The Approach to Typology of The Biocultural Landscape In Slovakia. - Izakovičová, Zita; Špulerová, Jana; Kozelová, Ivana (Environmental Management, 2022)
The European Landscape Convention aims to promote landscape protection, management and planning. This must be done based on identification and knowledge of those basic landscape types that were created by the interaction of human and nature over the course of historical development. This paper presents a methodological approach for creation and evaluation of representative biocultural types of landscape, in order to elaborate an effective strategy for landscape protection, and proposes a management strategy of sustainable use of representative biocultural landscapes of Slovakia. That will ensure the regular maintenance of the landscape in view of current global trends and factors affecting the landscape. Our interdisciplinary approach is based on previous landscape classifications and the interaction of natural and cultural elements. The classification of the biocultural landscape is obtained as a result of multi-criteria analysis in GIS and synthesis of maps of potential vegetation, real ecosystems and current land use, abiotic conditions of representative geoecosystems of Slovakia, and other specific statistical data. We assessed the perception and significance of individual landscape types by way of a questionnaire survey. In Slovakia, seven basic types of landscape were singled out, ranging from natural to semi-natural to anthropogenic, within which other subtypes were specified. We assessed the protection of individual types, as well as threats and degradation of the landscape. Insufficient protection is given to the most valuable types of biocultural landscape and new tools and methods of support and protection have to be implemented.